2014
DOI: 10.1890/es14-00092.1
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of global litter turnover rate predictions using a Bayesian MCMC approach

Abstract: Abstract. Global terrestrial carbon (C) cycle has a strong influence on atmospheric CO 2 concentrations and temperatures. Litter mass is relatively small in comparison to soil and plant pools but its turnover rate is fast. Litter dynamics is important part of the global terrestrial carbon cycle as it is a critical stage in the soil organic matter formation and nutrient mineralization. Litter turnover rates have been observed on site, regional, and global levels, however little effort has been put into validati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…This framework using matrix representation will also enable data assimilation to be easily applied in ecosystem models or other complex models. Model projections of ecosystem models such as the TECO model (Shi et al, ) or complex models such as global land C models (Hararuk et al, ; Hararuk & Luo, ; He et al, ) have been substantially improved via data assimilation using matrix representation of these models. Data assimilation technique was recognized as the highest priority to improve predictions of soil C dynamics in ESMs (Luo et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…This framework using matrix representation will also enable data assimilation to be easily applied in ecosystem models or other complex models. Model projections of ecosystem models such as the TECO model (Shi et al, ) or complex models such as global land C models (Hararuk et al, ; Hararuk & Luo, ; He et al, ) have been substantially improved via data assimilation using matrix representation of these models. Data assimilation technique was recognized as the highest priority to improve predictions of soil C dynamics in ESMs (Luo et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Long‐term soil manipulations [e.g., Lajtha et al , ; Melillo et al , ], accompanied by detailed measurements of microbial function, may be necessary to distinguish between alternative models of soil C response to changes in litter inputs or climate. Both first‐order and microbial‐explicit models could be improved and compared using such long‐term data sets and statistical approaches such as Bayesian data assimilation [ Hararuk and Luo , ; Tang and Zhuang , ; Wang et al , ; Xu et al , ]. The results of these analyses will be essential for improving soil C components of ESMs.…”
Section: Survey Of Current Microbial‐explicit Models (Including Drawbmentioning
confidence: 99%
“…Litterbags have been used extensively to examine the importance of different drivers and how they affect the nutrient and mineral fluxes from the plant litter to the soil (e.g., [5][6][7]). Based on a meta-analysis of 66 litterbag experiments involving 818 plant species, Cornwell et al [8] showed that within a climate region, plant species traits are important drivers of their litter decomposition.…”
Section: Introductionmentioning
confidence: 99%